Figura tradicional y figura disruptiva del padre en dos textos literarios latinoamericanos contemporáneos - López Badano, Cecilia; Acuña Murillo, Monserrat (Romanica Silesiana)
The figure of the father is presented in a variety of ways in contemporary Latin American literature; one of the popular images, for instance, is that of a despotic patriarchal “macho” in the drug trafficking literature. However, there is also a new image of paternity linked to “new masculinity,” presented as gender utopia in the short story “Alumbramiento” (“Birth”) by Andrés Neuman (2006). Here, a male narrator gives birth to a new man who is, at the same time, himself and his own son. In this article, I aim to explore the change from traditional images of paternity to the new, disruptive, utopian ones, inscribed within new ideas about gender equality.